Estimated genetic trends in the lysine requirements of growing-finishing pigs and reproductive sows due to genetic trends in production traits - Pieter W. Knap (Frontiers in Animal Science)
The requirements for standardized ileal digestible (SID) lysine due to lean tissue growth rate (LTGR) in growing-finishing pigs were quantified on the basis of data from the literature. The same was done for those requirements due to LTGR; protein deposition in mammary tissue, uterine tissue, fetal tissue and placental tissue; and colostrum and milk protein synthesis in gestating and lactating sows. These processes were expressed in terms of LTGR, litter size, piglet birth weight, preweaning survival rate, litter weaning weight and teat number. The 2013--2023 genetic trends of those traits in the PIC-L02, PIC-L03, PIC-L65 and PIC-L800 populations were estimated and converted to genetic trends in lysine requirements. On this basis, the daily SID lysine requirement of Camborough (i.e., PIC-L02 × PIC-L03) sows increases by 0.47 g/d (i.e., by 2% of the current mean level) per year: 0.10 g/d per year and 0.37 g/d per year for gestational and lactational processes, respectively. The daily SID lysine requirement of growing-finishing progeny of Camborough sows and either PIC-L65 or PIC-L800 boars increases by 0.09 g/d (i.e., by 0.6% of the current mean level) per year.